PRELIMINARY ACCOUNT OF THE EXPERIMENTAL ROCK-LOBSTER FISHING CONDUCTED ALONG THE SOUTH-WEST COAST OF INDIA WITH BOTTOM-SET GILL NETS - Balasubramanyan, R; Satyanarayana, A V V; Sadanandan, K A (Indian Journal of Fisheries, 2016)
The hard rocky bottoms of the sea below the tidal zone are usually the abode of the Rock Lobsters. They hide in the crevices and inside the holes of submerged rocks and lurk on stony corals and sea weed beds. Similar ecological conditions exist in certain areas off the East and West coast of India and is suggestive of an abimdance of this Decapod Crustacea. Though the resources for lobsters appear to be ext nsive, systematic exploitations have not so far been organised. From the available records of the total annual landing of shell-fishes in India, it has not been possible to assess the actual quantity of lobsters landed each year. During the preliminary survey conducted by the authors, it has been estimated that during the 1956-57 season about 5,95,000 lobsters weighing 1,13,400 kg. (2,50,0001b.) and valued at Rs. 1,98,000 were landed along the twenty mile stretch of the West Coast extending from Collachel to Kanyakumari. According to Miyamoto and Shariff" (1958) in Muttam village alone during 1957-58 season about 53,998-4 kg. (1,19,0441b.) of lobsters were landed. Chacko and George (1958) have recorded that in a good fishing season 6,500 lobsters can be collected per day from Muttam and nearby villages.